1996
DOI: 10.1111/j.1365-2648.1996.tb03131.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the professional code still the cornerstone of clinical nursing practice?*

Abstract: Although codes of practice for those concerned with the health care of others have always been inherent in the structure of societies, they have been institutionalized within the nursing discipline since the end of the last century. Up until the early 1970s they promulgated subservience to the medical discipline. As a result of the processes of emancipation and professionalization, the philosophy of the nurse has come to contain concepts of autonomy, accountability and patient-advocacy, based on a personal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…An opposite position is taken by Pattison (2001) and Thompson (2002), who both have argued that professional codes suffer from terminological inexactitudes and confusions as well as arbitrariness in values and principles. Empirical studies have also shown (Esterhuizen, 1996;Höglund, 2005) that nurses make ethically sound choices based on their own decision-making ability, while having little or no active knowledge of existing professional codes or ethical guidelines.…”
Section: Background: Ethical Competencementioning
confidence: 96%
“…An opposite position is taken by Pattison (2001) and Thompson (2002), who both have argued that professional codes suffer from terminological inexactitudes and confusions as well as arbitrariness in values and principles. Empirical studies have also shown (Esterhuizen, 1996;Höglund, 2005) that nurses make ethically sound choices based on their own decision-making ability, while having little or no active knowledge of existing professional codes or ethical guidelines.…”
Section: Background: Ethical Competencementioning
confidence: 96%
“…However, research shows that many practicing nurses are not familiar with their professional codes and few nurses actually rely on these codes when making ethical decisions. 19 According to Ham 14 practicing nurses do not seek out continued education in the area of ethics and tend instead to focus on continuing education that focuses on their specialty areas of practice.…”
Section: Influencers Of Ethical Beliefsmentioning
confidence: 99%
“…Similarly transferable is the conclusion that if interpreted in a literal way, codes produce the opposite effect from that intended, forcing nurses to disguise their errors and not making accurate reports (Esterhuizen, 1996); the professional's commitment to act rightly according to moral standards is transferred to a focus on compliance with the code (Pattison, 2001). Yoder (1998) sees ethical expertise as interdisciplinary and, therefore, wider than clinical expertise, with codes unable to replace a professional's ethical sensitivity and individual decision making.…”
Section: Professional Identitymentioning
confidence: 99%